Gabriel-Cromwell aziridination of amino sugars; chiral ferrocenoyl-aziridinyl sugar synthesis and their biological evaluation. (November 2021) - Sert, Mustafa; Işılar, Özer; Yaglioglu, Ayse Sahin; Bulut, Adnan
Abstract: N -sugar substituted chiral aziridines were synthesized via Gabriel-Cromwell reaction. Novel pure diastereomers of aziridine derivatives (4 diastereomers) were readily obtained in high yields and their structures were confirmed by means of 1 H NMR, 13 C NMR, FT-IR, Mass and optical rotations. This is, to the best of our knowledge, the unique example of N -sugar aziridine synthesis. Diastereomeric effects for prostate (PC3) and cervix (HeLa) cancers were screened and it has been observed that the epimers bearing the same sugars showed different results against PC3 and HeLa cancer cells. The novel sugar aziridines were investigated as promising prodrug candidates for prostate cancer (PC3) therapy. Moreover, the drug likeness calculations (Lipinski's rule, physicochemical properties, lipophilicity, solubility, pharmacokinetics and bioavailability radar) have indicated that the sugar aziridines can be good candidates as oral drugs. Graphical abstract: Image 1 Highlights: Aziridinyl sugars were synthesized for the first time by the Gabriel-Cromwell reaction. Ferrocene-containing aziridinyl sugar diastereomers were easily separated from each other by flash column chromatography. Ferrocene-Aziridine-Sugar diastereomers are promising prodrug candidates for prostate cancer (PC3) therapy.